2020
DOI: 10.1038/s41556-020-0562-4
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation-dependent regulation of PD-L1 nuclear translocation dictates the efficacy of anti-PD-1 immunotherapy

Abstract: Immunotherapies targeting programmed cell death protein 1 (PD-1) and its ligand PD-L1 as well as cytotoxic T-lymphocyte-associated protein 4 (CTLA4) have shown impressive clinical outcomes for multiple tumours. However, only a subset of patients achieves durable responses, suggesting incompletely understood mechanisms of the immune checkpoint pathways. Here, we report that PD-L1 translocates from the plasma membrane into the nucleus through interaction with components of endocytosis and nucleocytoplasmic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
261
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(280 citation statements)
references
References 68 publications
(64 reference statements)
17
261
0
2
Order By: Relevance
“…Here, we show that demethylation of ACE2 in the cytoplasmic tail is required for interaction with the importin-α complex and nuclear translocation. This is similar to recent findings showing that the immune checkpoint protein PD-L1, a major immunotherapy target, also translocates to the nucleus to control transcription in an importin-α-dependent manner via PTM regulation of its cytoplasmic tail through the non-histone role of epigenetic enzymes 77 . Furthermore, other important receptors such as EGFR also have nuclear functions mediated by PTMs catalyzed by epigenetic enzymes that allow nuclear translocation 78 .…”
Section: Discussionsupporting
confidence: 90%
“…Here, we show that demethylation of ACE2 in the cytoplasmic tail is required for interaction with the importin-α complex and nuclear translocation. This is similar to recent findings showing that the immune checkpoint protein PD-L1, a major immunotherapy target, also translocates to the nucleus to control transcription in an importin-α-dependent manner via PTM regulation of its cytoplasmic tail through the non-histone role of epigenetic enzymes 77 . Furthermore, other important receptors such as EGFR also have nuclear functions mediated by PTMs catalyzed by epigenetic enzymes that allow nuclear translocation 78 .…”
Section: Discussionsupporting
confidence: 90%
“…However, a recent study revealed that nuclear PD-L1 has intrinsic functions that disrupt the effectiveness of anti-PD-1 immunotherapy. It demonstrated that PD-L1 nuclear translocation is controlled by acetylation and is associated with the efficacy of PD-1/PD-L1 targeted immunotherapy [ 60 ]. Furthermore, nuclear PD-L1 regulates several genes involved in immune responses, including NF-κB signal-related genes and major histocompatibility complex class I [ 59 , 60 , 61 ].…”
Section: The Role Of Yap In Tumor Immunity and Microenvironmentmentioning
confidence: 99%
“…Under hypoxia treatment, p-Stat3 physically interacts with PD-L1 and facilitates its nuclear translocation [ 41 ]. Another report found that deacetylation of PD-L1 at Lys 263 by HDAC2 triggers nuclear translocation by interacting with multiple proteins that are involved in endocytosis and nuclear import like HIP1R, vimentin [ 42 ]. Here in our study, we found that KPNB1 was the most relevant protein with PD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent new findings showed that nPD-L1 and p-Y705-Stat3 acted as co-activators in regulating GSDMC mRNA expression and then switched apoptosis to pyroptosis [ 41 ]. Moreover, nPD-L1 interacted with STAT3, c-Jun to govern immune-response-related genes expression and thereby modulated the anti-tumour immune response [ 42 ]. Sp1 is well identified as a common transcription factor that recognises the GC-rich DNA sequences in the promoter regions of various genes [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%